A sticky situation: methaemaglobinaemia in a hand trauma patient. (12th November 2012) - Sheena, Yezen; Baston, Emma Louise; Downs, Andrew; Chester, Darren L
Abstract : We describe a case of methaemoglobinaemia (MtHb) in a previously healthy 39-year-old gentleman who presented with a traumatic glass laceration to his right wrist that required emergency surgery to control bleeding and repair his ulnar artery. The MtHb was noted on blood gas analysis by the anaesthetist after the patient had a drop in arterial oxygen saturation under general anaesthetic. We initially suspected the lidocaine local anaesthetic injected proximal to his wound for pain control in the emergency department an hour preoperatively, but then discovered that the patient was a recreational user of 'poppers' and had in fact been using these drugs just before his injury and hospitalisation. The patient's condition stabilised overnight with conservative management. Given how commonly hand surgeons and other clinical staff use local anaesthetics, we reviewed the literature on this uncommon, but potentially fatal, complication, its causes and evidence-based management.